IJIS Edu : Indonesian J. Integr. Sci. Education, 5 (1) 2023 Copyright © 2023, Jelika Aulia, Suyud Abadi, Rindi Novitri Antika 48 The Effect of Problem Based Learning Models on Student Learning Outcomes in Material Structure and Functions of Plants - Aulia, Jelika; Abadi, Suyud; Antika, Rindi Novitri (IJIS Edu : Indonesian Journal of Integrated Science Education, 2023)
This study aims to determine the effect of the Problem Based Learning (PBL) model on studentlearning outcomes on plant structure and function material. This research is a quasi-experimental study witha pretest-posttest control group design. The population of this research is SMP Muhammadiyah 1Palembang students. The sample in this study were students of class VIIIA as the experimental class andVIIIB as the control class which were selected by purposive sampling. The learning outcomes analyzed arecognitive learning outcomes. Test analysis using independent sample T-test. The results showed that therewas an influence of the Problem Based Learning model on students' cognitive learning outcomes, it wasknown from the sig value on the t test 0.038 <0.05. Then it is supported by the average post-test score ofthe experimental class (82.46) which is higher than the control class (73.50).